Shrinkage Estimation of Cast Al–Si Alloys through Process Simulation - Santhi, Samavedam; Sundarrajan, Srinivasan (Металлофизика и новейшие технологии, 2017)
With the advent of various casting process simulation techniques, it is possible to derive theoretically casting parameters, which can be further validated through experiments. In this paper, detailed simulation activities are carried out to determine the shrinkage characteristics of two Al–Si alloys (US 413 and US A356) followed by validation through experimental studies. Production of defect-free castings requires good understanding of shrinkage characteristics. The influence of various process parameters on these characteristics determines the casting quality. Based on this, an extensive study is undertaken to comprehend the influence of various parameters.